2001
DOI: 10.1097/00002030-200108004-00013
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting sexual behaviour data: validity issues in the multicentre study on factors determining the differential spread of HIV in four African cities

Abstract: In all four cities, we found evidence that men as well as women misreported their sexual behaviour, but overall it seems that under-reporting of sexual activity was not more common or more serious in the two high HIV prevalence cities than in the two low HIV prevalence cities. We believe that the main conclusions of the multicentre study still hold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 3 publications
3
84
0
Order By: Relevance
“…5 When valid data on sexual behaviour change are required, period effects can pose additional challenges. 6 For example, sexual behaviour in men in Zimbabwe is associated with length of time since last pay day. 7 Respondents interviewed at different times of the month in successive rounds of a survey may appear to have changed their behaviour when this has not, in fact, been the case.…”
mentioning
confidence: 99%
“…5 When valid data on sexual behaviour change are required, period effects can pose additional challenges. 6 For example, sexual behaviour in men in Zimbabwe is associated with length of time since last pay day. 7 Respondents interviewed at different times of the month in successive rounds of a survey may appear to have changed their behaviour when this has not, in fact, been the case.…”
mentioning
confidence: 99%
“…First, simulation outcomes are very sensitive to the assumptions considered, first among which is the level of sexual activity. The CHFLS may understate the level of sexual activity owing to an understatement of stigmatized behavior, a feature generally common to surveys of sexual behavior, especially among women (Buvé et al 2001;Mensch, Hewett, and Erulkar 2003;Curtis and Sutherland 2004). In previous work we have shown the sensitivity of simulated HIV prevalence to changes in the levels of sexual activity, with a larger epidemic produced by a hypothetical higher rate of partner change consistent with levels of sexual activity observed in the U.S., which are higher than those in China (Merli et al 2006).…”
Section: Summary and Discussionmentioning
confidence: 59%
“…A first insight can give the Multicentre Study of Factors Determining the Different Prevalences of HIV in Sub-Saharan Africa, which estimated the magnitude of misreporting by testing for various sexually transmitted infections among women aged 15-24 years who reported that they had never had sexual intercourse (Buvé et al 2001b). The study concludes that between 6 and 18% of women had misreported their sexual activity.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies however, report a positive association between HIV infection and wealth (see for example Lachaud 2007, Mishra et al 2007. (4) A high HIV prevalence in adolescent women who report that they have not initiated sexual activity is found by Gavin et al (2006) and Buvé et al (2001b).…”
Section: Introductionmentioning
confidence: 99%